Overexpression of Calretinin Enhances Short-Term Synaptic Depression - Bolshakov, Alexey P.; Kolleker, Alexander; Volkova, Evgenia P.; Valiullina-Rakhmatullina, Fliza; Kolosov, Peter M.; Rozov, Andrei (Frontiers in Cellular Neuroscience, 2019)
Analysis of the effects of various proteins on short-term synaptic plasticity is a difficult task, which may require the use of knockout animals. Here, we propose alternative experimental approach for studying the roles of desired proteins in synaptic plasticity. We packed Ca2+-binding protein calretinin and fluorescent protein Venus into AAV and injected the concentrated viral suspension into the neocortex of newborn rats. The infected layer 2/3 pyramidal cells were identified in rat cortical slices using Venus fluorescence. Analysis of short-term synaptic plasticity using paired patch clamp recordings between layer 2/3 pyramidal cells (presynaptic cell) and fast-spiking interneurons (postsynaptic cell) showed that calretinin expression in the pyramidal cells did not change the failure rate in this synapse but did decrease synaptic delay. Analysis of the parameters of short-term synaptic plasticity showed that the amplitude of the first EPSP in the train was not affected by calretinin, however calretinin strongly enhanced short-term depression. In addition, we found that the effect of calretinin depended on the presynaptic firing frequency - an increase in frequency resulted in enhancement of synaptic depression.